Be in art: ways of recognition - Otero Caicedo, Liliana; Fernandez Moreno, Aleida (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2017)
This research experience was intended to generate creative reflections, felt and embodied around the experiences of recognition that people with dis_ability Moon Art Foundation live in their artistic journeys from the perspective of Axel Honneth. These reflections are born from the metaphorized bodies in body maps since the Arts-based Research as study methodology. It mainly concludes that the enjoyment and participation in the artistic life contributes to social esteem of this population and therefore the enhancement of their skills, qualities and valuation of their contributions within their community.